Energy Efficient Self-Healing Routing Protocol In Wireless Sensor Network - PONNUSAMY, VASAKI (2012)
Wireless sensor networks (WSN) are gaining popularity in pervasive environments for tracking events such as habitat monitoring, weather monitoring, hazard detection etc. These sensor nodes are very much power constrained and therefore require energy efficient protocols to efficiently manage their energy resources. As sensor nodes are highly resource constrained, energy efficient communication becomes one of the main issues to be dealt with. In sensor networks, transmission of data between nodes incurs the highest energy consumption followed by the distance, in which energy consumed is directly proportional to the square of the distance between the sender and receiver. One of the potential problems with current routing protocols is that, they look for the lowest energy route and use that route for every communication and causes energy depletion along this particular path. This is one of the main issues to be addressed by this research and which can be overcome by the proposed Biologically-Inspired Mobile Agent based Sensor Network (BIMAS) architecture, for mobile WSN. For the proposed mobile WSN, an optimal mobility pattern is chosen so that nodes closer to the sink are not utilized the most to prevent routing holes. The entire data aggregation and forwarding of data to a base station is taken care by mobile nodes themselves. BIMAS addresses the energy issues by exploiting mobile agents that communicate with static sensor nodes and forward sensed data to a base station. The mobile agents have the benefit of elevating the routing issues away from sensor nodes to the mobile agents. The advantages of BIMAS include efficient energy resources, fault-tolerance and efficient handling of routing hole problems. In BIMAS, the mobile agent based sensor is able to look into possible options to increase network lifetime through conserving energy at the sensor nodes. The adoption of bee communication based idea in this research gives insights into how mobile agents can perform its role in data collection and energy provisioning techniques as it is performed in the biological system.